Highly Invasive Fluorescent/Bioluminescent Patient-Derived Orthotopic Model of Glioblastoma in Mice - Yuzhakova, Diana; Kiseleva, Elena; Shirmanova, Marina; Shcheslavskiy, Vladislav; Sachkova, Daria; Snopova, Ludmila; Bederina, Evgeniya; Lukina, Maria; Dudenkova, Varvara; Yusubalieva, Gaukhar; Belovezhets, Tatyana; Matvienko, Daria; et al. (Frontiers in Oncology, 2022)
Development of the novel diagnostic and therapeutic approaches in neuro-oncology requires tumor models that closely reproduce the biological features of patients' tumors. Patient-derived xenografts (PDXs) recognized as a valuable and the most “close-to-patient” tool for preclinical studies. However, their establishment is complicated by the factors related both to the surgical material and technique of the orthotopic implantation. The aim of this work was to develop a patient-derived glioblastoma multiform (GBM) model that stably coexpress luciferase and a far-red fluorescent protein for monitoring of tumor progression in the brain and, using this model, to validate new diagnostics methods - macroscopic fluorescence lifetime imaging (macro-FLIM) and cross-polarization optical coherence tomography (CP OCT). The established model was similar to the original patient’GBM in terms of histological and immunohistochemical features, and possessed reproducible growth in nude mice, which could be observed both by fluorescence and bioluminescence imaging. Our results demonstrated the high potential of macro-FLIM and CP OCT for intraoperative differentiation of GBM from the white matter and suggested the diversity of metabolic phenotypes in patient’s GBM. Thus, the dual-labeled PDX model of GBM proved to be an excellent approach for observation of tumor development by optical methods.